The Undeniable Role That Campus Recreation Programs Can Play in Increasing Indigenous Student Engagement and Retention. Issue 2 (October 2019) - Dyk, Chad Van; Weese, W. James
Leaders at Canadian universities seek to attract and graduate more Indigenous students as part of their institutions' strategic plans. Admissions and student retention data suggest that while progress is being made, a gap remains between Indigenous and non-Indigenous students and especially in the student retention area. Research has proven that student engagement plays a large role in facilitating academic progression and student retention in our institutions of higher learning. Throughout time, many students point to their experience as campus recreation program participants and/or leaders as their most important source of engagement. Some have suggested that campus recreation programs could play a larger and more effective role in engaging Indigenous students and heightening their retention rates. In this conceptual article, the authors analyze the student engagement and retention literature bases relative to Indigenous students. They also highlight the role that campus recreation programs can play in heightening Indigenous student engagement and retention and offer professionals 12 recommendations to help advance this strategic priority.